Tathwîr Wasîlah at-Ta’lîm al-Bashariyyah al-Mutaharrikah al-Qâimah ‘alâ Android fî Tadrîs at-Tarkîb - Ayu Nurhidayati Nurhidayati; Erlina Erlina; Umi Hijriyah; Guntur Cahaya Kesuma (Postgraduate of IAIN Metro Lampung Indonesia, 2022)
The lack of learning media in the Arabic learning process makes it difficult for students to understand the material and feel bored and they think that learning Arabic is very difficult, especially in understanding material about tarkib or Arabic rules. With these problems, the researchers developed an android application-based tarkib learning media for 7th grade junior high school students, with the hope of facilitating student understanding and being effective in its use. The method used in this research is research and development. The result of this research is that the learning media is suitable for students to use as learning media and is effective in its use.